ANALISIS TUJUAN PEMIDANAAN DALAM PEMBARUAN HUKUM PIDANA NASIONAL TERKAIT TINDAK PIDANA ADAT (STUDI DELIK ADAT BALI) - I Wayan Suardana; I Made Walesa Putra (VYAVAHARA DUTA, 2021)
Reform of the National Criminal Law is absolutely necessary with political, practical and sociological considerations. The amend of Criminal Code also include adjustments of the punishment aims, which leads to restorative justice. Likewise the sanctions for criminal offense in adat law, the punishment is less than optimal if only imposed the freedom deprivation to the perpetrator's, it is necessary to make efforts in restoring the situation (balance).This type of research is normative research, by analyzing norms and legislation related to the aim of punishment in customary offenses. The results of the research that is the aim of customary sentencing is not specifically regulated in positive law, but customary criminal law have the power to apply, based: Article 18 B paragraph (2) of The 1945 State Constitution of the Republic of Indonesia, Emergency Law No. 1 of 1951 on Temporary Measure in Organizing the Unity of the powers and procedure of Civil Courts, Law No. 48 of 2009 on Judicial Power, Law No.39 of 1999 on Human Rights, and the Supreme Court Decisions, among others: (1) Decision No. 1644K / Pid / 1988 dated May 15, 1991; (2) Decision No. 984 K / Pid / 1996 dated January 30, 1996.In the positive law, there is a reflection of restorative justice as a concept that developed in modern criminal law in line with the purpose of sentencing the customary offenses. The aim of sentencing as ius constituendum is formulated in Article 55 paragraph (1) of the 2017 Criminal Code Concept which includes resolving conflicts that arise, restoring balance, and bringing sense of peace and secure in the community, which is in line with customary criminal sanctions because of the visible values of customary law; resolve conflicts, restore balance, and bring a sense of peace in society.